Financial management : theory and practice - Brigham, Eugene F., 1930- (SOUTH-WESTERN CENGAGE Learning, 2014)
From the publisher. Striking a balance between solid financial theory and practical applications, Brigham/Ehrhardt's Financial Management: Theory and Practice, 14th edition, gives readers a thorough understanding of the essential concepts they need to develop and implement effective financial strategies. The book begins with a presentation of corporate finance fundamentals before progressing to discussions of specific techniques that are used to maximize the value of a firm. It also thoroughly explores the recent financial and economic crises and the role of finance in the business world and in readers' personal lives. With its relevant and engaging presentation, cutting-edge coverage, and numerous examples, Financial Management help readers become first in finance.